2008
DOI: 10.1074/jbc.m801376200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Arabidopsis Heterotrimeric G Protein

Abstract: We have used fluorescence resonance energy transfer and coimmunoprecipitation to analyze the interactions among the ␣, ␤, and ␥1 subunits of the Arabidopsis heterotrimeric G protein.Using cyan and yellow fluorescent protein fusion constructs, we show that overexpressed G␥ 1 localizes to protoplast membranes, but G␤ exhibits membrane localization only when the G␥ 1 protein is co-overexpressed. Overexpressed G␣ shows membrane localization unaccompanied by overexpression of either G␤ or G␥ 1 . We detect fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 63 publications
(89 reference statements)
5
62
0
1
Order By: Relevance
“…This view is consistent with the recent discovery of the Arabidopsis Ga-subunit gene GPA1 as a central element in ABAdependent innate immunity in stomatal guard cells . Moreover, there is ample evidence indicating that ABA signaling processes in both seeds and guard cells involve components of the heterotrimeric G-protein complex, further supporting our hypothesis (Pandey and Assmann, 2004;Fan et al, 2008;Wang et al, 2008). According to the G-protein signaling paradigm, the lack of Ga not only abolishes Ga-mediated signaling but also results in free Gbg, thereby possibly enhancing Gbg signal output (Pandey et al, 2006).…”
Section: Discussionsupporting
confidence: 60%
“…This view is consistent with the recent discovery of the Arabidopsis Ga-subunit gene GPA1 as a central element in ABAdependent innate immunity in stomatal guard cells . Moreover, there is ample evidence indicating that ABA signaling processes in both seeds and guard cells involve components of the heterotrimeric G-protein complex, further supporting our hypothesis (Pandey and Assmann, 2004;Fan et al, 2008;Wang et al, 2008). According to the G-protein signaling paradigm, the lack of Ga not only abolishes Ga-mediated signaling but also results in free Gbg, thereby possibly enhancing Gbg signal output (Pandey et al, 2006).…”
Section: Discussionsupporting
confidence: 60%
“…Interestingly, we observed strong direct binding between XLGs and Gg subunits even in the absence of Gb using protoplasts derived from the agb1-2 mutant. By contrast, interaction between Ga and Gg1 was detected only when Gb was present (Wang et al, 2008). This fact emphasizes the diversification between XLGs and plant Gas but is not unprecedented because it has been demonstrated that the human Ga subunit Ga o directly interacts with the Gg2 subunit (Rahmatullah and Robishaw, 1994).…”
Section: Discussionmentioning
confidence: 87%
“…Further biochemical studies are required to establish if the XLGGbg interaction is nucleotide dependent (Wall et al, 1995;Digby et al, 2006) or follows the alternative, nondissociable activation mechanism (Bünemann et al, 2003;Galés et al, 2006). Interestingly, while, in rice, the nonhydrolysable nucleotide GTPgS caused full dissociation of Ga from the complex (Kato et al, 2004), only about 30% of Ga was dissociated in Arabidopsis (Wang et al, 2008). Moreover, a mutated GPA1, which is unable to hydrolyze GTP and hence constitutively active, was found in a complex with Gbg1 (Adjobo-Hermans et al, 2006), suggesting that, in Arabidopsis, this canonical heterotrimer does not dissociate upon activation and therefore the Ga/Gbg interaction is not entirely nucleotide dependent.…”
Section: Discussionmentioning
confidence: 99%
“…The RNS2 cDNA (6) was obtained from Pamela Green (University of Delaware, Newark, DE). The CFP-coding region was amplified from pAVA321-CFP (37). The cauliflower mosaic virus 35S promoter was obtained from the pGD vector (38).…”
Section: Methodsmentioning
confidence: 99%